2020
DOI: 10.1038/s41598-020-68372-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of lung function with overall mortality is independent of inflammatory, cardiac, and functional biomarkers in older adults: the ActiFE-study

Abstract: Reduced lung function is associated with overall and cardiovascular mortality. Chronic low grade systemic inflammation is linked to impaired lung function and cardiovascular outcomes. We assessed the association of lung function with overall 8-year mortality in 867 individuals of the Activity and Function in the Elderly study using confounder-adjusted Cox proportional hazards models (including gait speed and daily walking time as measures of physical function) without and with adjustment for inflammatory and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“… 34 Even after adjusting physical function and inflammatory and cardiac markers, FEV 1 /FVC was independently associated with mortality. 35 In particular, decreased FEV 1 or worsened airflow limitation was associated with increased cardiovascular mortality. 36 Among the several clinical variables that have been considered to mediate the relationship between airflow limitation and mortality, chronic systemic inflammation might be the most important explanatory factor.…”
Section: Discussionmentioning
confidence: 98%
“… 34 Even after adjusting physical function and inflammatory and cardiac markers, FEV 1 /FVC was independently associated with mortality. 35 In particular, decreased FEV 1 or worsened airflow limitation was associated with increased cardiovascular mortality. 36 Among the several clinical variables that have been considered to mediate the relationship between airflow limitation and mortality, chronic systemic inflammation might be the most important explanatory factor.…”
Section: Discussionmentioning
confidence: 98%
“…Given this health pattern, identification of potential predictors of mortality in this region is pivotal. Association of reduced spirometry indices with overall mortality has been well established in western populations [ 1 , 5 , 6 , 8 , 28 ]. The findings that all-cause mortality increased with the severity of lung function impairment are in accordance with a previous cohort study of elderly individuals [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have investigated the role of impaired lung function in risk of mortality [ 1 6 ]. It has been shown that reduced levels of forced expiratory volume measured in one second (FEV1) [ 3 , 7 , 8 ] and/or forced vital capacity (FVC) [ 9 , 10 ] are good predictors of all-cause mortality in general population.…”
Section: Introductionmentioning
confidence: 99%
“…Lung function, especially the forced expiratory volume in 1 s (FEV 1 ), is an independent predictor of mortality in individuals with or without chronic lung diseases. [1][2][3][4] In the seminal randomized controlled trials to evaluate the efficacy of biologics in asthma, longitudinal trajectories of the pre-bronchodilator FEV 1 , [5][6][7][8][9][10] or the change in FEV 1 from baseline to a specific time point over follow-up, [11][12][13] were the outcomes of interest. These studies showed modest to great improvement in the prebronchodilator FEV 1 in patients with moderateto-severe asthma over relatively short follow-up periods.…”
Section: Introductionmentioning
confidence: 99%